Combined Methylglyoxal Scavenger and Collagen Hydrogel Therapy Prevents Adverse Remodeling and Improves Cardiac Function Post‐Myocardial Infarction. (12th October 2021) - Cimenci, Cagla Eren; Blackburn, Nick J. R.; Sedlakova, Veronika; Pupkaite, Justina; Munoz, Marcelo; Rotstein, Benjamin H.; Spiegel, David A.; Alarcon, Emilio I.; Suuronen, Erik J.
Abstract: Methylglyoxal (MG) is a highly reactive dicarbonyl and the main precursor of advanced glycation end‐products (AGEs). After myocardial infarction (MI), MG‐derived AGEs accumulate in the heart and contribute to adverse remodeling and loss of cardiac function. In this study, the flavonoid fisetin, a dicarbonyl scavenger, is used to reduce the negative effects of MG in the post‐MI heart. A fisetin‐loaded collagen type I hydrogel (fisetin‐HG) is injected intramyocardially in mice at 3 h post‐MI, and compared to fisetin‐alone, hydrogel‐alone, or saline treatment. Fisetin‐HG treatment increases the level of glyoxalase‐1 (the main MG‐metabolizing enzyme), reduces MG‐AGE accumulation, and decreases oxidative stress in the MI heart, which is associated with smaller scar size and improved cardiac function. Treatment with fisetin‐HG also promotes neovascularization and increases the number of pro‐healing macrophages in the infarct area, while reducing the number of pro‐inflammatory macrophages. Taken together, the results demonstrate that the fisetin‐collagen hydrogel therapy can reduce the accumulation and negative effects of MG post‐MI. This therapy may be a promising approach to limit adverse cardiac remodeling, prevent damage, and preserve function of the infarcted heart. Abstract : A combination of the antioxidant fisetin with a collagen hydrogel is used to treat MI. The treatment decreases MG‐related oxidative stress and protects the myocardium through stimulating the activity of Nrf2, Glo1, and GSH, which are known to contribute to MG detoxification. This constitutes a new therapeutic approach to limit damage and improve cardiac function after MI.